Content Analysis Of Customers’ Negative Reviews Of An Indonesian Online Travel Agency On The Google Play APP - Kanya Anindita; Siswantini Siswantini; Divya Thanra; Farasiva Indiani Rajasa (Cakrawala Repositori IMWI, 2023)
This research delves into the nature of negative reviews that customers post about the OTA platform on Google Play, and how the OTA responds to them. It takes a qualitative approach and uses content analysis to analyze negative reviews posted between November 2022 and January 2023. The study revealed that customers' negative reviews were related to various aspects of the user experience, such as issues with the Paylater feature, refunds, third-party services, errors, and cancellations. The study further identified several phrases that customers frequently used to express their dissatisfaction with the OTA platform. This information can be helpful to the OTA in identifying specific areas that require improvement and in creating effective customer experience management strategies. The findings of this research provide useful insights into customer perceptions of the OTA platform, which can inform OTA's decision-making processes. The OTA can use this information to address the specific concerns raised by customers and improve their overall experience with the platform. Ultimately, the research can assist the OTA in enhancing its reputation, improving customer loyalty, and gaining a competitive advantage in the market.